Harbor water pollution by heavy metal concentrations in sediments - L. Sulistyowati; Y. Yolanda; N. Andareswari (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The Belawan Harbor is the third largest port, which is located in an estuary, causing the port water area to be vulnerable to pollution, especially heavy metals. Conflicts between the community and the port authorities often occur due to pollution. Heavy metals are dangerous contaminants for waters, and total organic carbon in waters is needed but will cause eutrophication if the concentration is excessive in the environment. The level of heavy metal pollution in the waters of the Belawan Harbor and the factors that cause the pollution should be analyzed, because the level of heavy metal pollution has not been measured in the sediments of harbor waters. This study can be used as a reference for the actions of related agencies in dealing with heavy metal pollution in waters.METHODS: Sampling of sediments was performed at 10 locations, starting before the harbor activity began and moving toward the open sea. Sampling was conducted using Van Veen grab. Heavy metal concentrations were analyzed in the laboratory using the atomic absorption spectrometer method to assess the essential heavy metal copper and non-essential heavy metal lead, cadmium, and mercury. Heavy metal pollution in sediments was assessed by analyzing sediment pollution index. The multivariate statistical analysis on the relationship among factors was conducted using Pearson correlation matrix method, principal component analysis, and cluster analysis.FINDINGS: The environmental quality standards used indicate average concentration of heavy metals; lead (28,869 milligram per kilogram) and copper (8,003 milligram per kilogram) are below the quality standard. The mercury concentrations are undetectable (<0.00011 milligram per kilogram) at each station. By comparison, the concentration of cadmium (1,455 milligram per kilogram) exceeded the Interim Sediment Quality Guidelines from the Canadian Council of Ministers of the Environment. Results of the index analysis show that the average value of the pollution factor of copper is −0.177 (low contamination), that of lead is −1.433 (moderate contamination), and that of cadmium is −4.850 (high contamination); the geoaccumulation index value of copper is −5.328. (not polluted), that of lead is −0.190 (unpolluted), and that of cadmium −1.657 (moderately polluted). As mercury concentration in sediments is relatively low, it is not considered when calculating pollution levels. Overall, on the basis of a pollution index of 1.033 (1 < pollution load index ≤ 2), this condition indicates that the waters of the Belawan Harbor are categorized as not polluted to lightly polluted. The highest total organic carbon is at the estuaries of the Belawan and Deli Rivers. The sediment fraction is 72.2 percent sandy, 16.4 percent sludge, and 11.4 percent clay substrate.CONCLUSION: Pollution in the waters of the Belawan Harbor is in the category of not polluted to slightly polluted. Although the pollution is still in the light category, this must be of particular concern to the relevant agencies, especially the local government, to make the right policies to overcome this pollution immediately. Pollution problems increase with the anthropogenic activities around coastal areas, as well as activities in the Belawan and Deli River watersheds, because the pollutant will flow from the upstream to the estuary area.